Formação de biofilmes monotípicos e heterotípicos por Enterococcus faecalis E Enterococcus faecium em dentina radicular - Santos, Ana Carolina Chipoletti dos [UNESP] (2018)
E. faecalis and E. faecium have a high relevance in hospital infections because they are easy to acquire resistance to antibiotics. E. faecalis also present high prevalence in endodontic infections, however the importance of E. faecium for dentistry still needs to be clarified. Thus, the objective of this study was to compare clinical strains of E. faecium with strains of E. faecalis in relation to the capacity of biofilm formation in root dentin and penetration into the dentin tubules. In addition, the interaction of these species in mixed biofilms was evaluated. In order to perform this study, clinical strains were used, pre-determined, isolated from root canals with endodontic infections and identified by multiplex PCR. Among the isolated strains, 4 strains of E. faecalis and 2 strains of E. faecium were selected. Firstly, the formation of the monotypic biofilms of the strains of E. faecalis and E. faecium on root dentin of bovine teeth was carried out. The biofilms were formed in microtiter plates at different times: 2, 4, 6, 24, 48, 72, 96 and 120 hours. The biofilms formed were then analyzed by counting viable cells (CFU / mL) and quantification of total biomass (violet crystal method). In addition, the biofilms were analyzed by Scanning Electron Microscopy (SEM), aiming to observe the penetration of E. faecalis and E. faecium cells into the dentin tubules. Then, heterophilic biofilms of E. faecalis and E. faecium were formed to study the ecological interactions established between the species. The analysis of the heterotypic biofilms was made by quantifying the total biomass (violet crystal) in order to detect the presence of synergistic or antagonistic relationships The results were submitted to Analysis of Variance (ANOVA) and Tukey test, considering a level of 5%. The results obtained in the CFU / mL count of the monotypic biofilms revealed that the six strains tested had a great capacity to form biofilms in the root dentin, reaching values of CFU / mL between 8 and 12 log according to the time of observation. In relation to SEM images, the clinical strains of E. faecalis and E. faecium demonstrated similar capacity to form biofilms and to penetrate the dentinal tubules. In the comparison of the biomass quantification of the monotypic and heterotypic biofilms, we observed that the interaction of the clinical strains E. faecalis and E. faecium favored the adhesion and growth of the biofilm. Thus, it was concluded that strains of E. faecalis and E. faecium have the same ability to form biofilms on the root surface. In addition, in mixed biofilms, these two species establish synergistic ecological relationships, significantly increasing the formation of biofilms.